2020
DOI: 10.21203/rs.3.rs-48709/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bisindolylmaleimide IX: A novel anti-SARS-CoV2 agent targeting viral main protease 3CLpro demonstrated by virtual screening and in vitro assays

Abstract: The emergence of SARS/MERS drug-resistant SARS-CoV2 comes with higher rates of transmission and mortality. Like all coronaviruses, SARS-CoV-2 is a relatively large virus consisting of several enzymes with essential functions within its proteome. Here, we focused on repurposing approved and investigational drugs by identifying potential drugs that are predicted to effectively inhibit critical enzymes. We targeted seven proteins with enzymatic activities known to be essential at different stages of the viral mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…In the present study, through the application of in-silico based virtual screening of FDA and world approved drugs [ 23 ] and specific in-vitro validations, we found that UFH had a sub-nanomolar activity and a potential to block receptor-binding domain (RBD) of SARS-CoV-2, thus pointing to its immense potential as a transmission-blocking agent. Collectively, the current findings emphasize the possible beneficial use of heparin, both as a transmission-blocking agent and treatment for coagulopathy/DIC associated symptoms in severe COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, through the application of in-silico based virtual screening of FDA and world approved drugs [ 23 ] and specific in-vitro validations, we found that UFH had a sub-nanomolar activity and a potential to block receptor-binding domain (RBD) of SARS-CoV-2, thus pointing to its immense potential as a transmission-blocking agent. Collectively, the current findings emphasize the possible beneficial use of heparin, both as a transmission-blocking agent and treatment for coagulopathy/DIC associated symptoms in severe COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nonstructural uridylate-specific endoribonuclease (NendoU) is another nonstructural protein worth investigating as an antiviral target since its endoribonuclease is suspected to be similar in all coronaviruses. 23,24 Angiotensin-converting enzyme 2 (ACE2) is an antigen receptor recognition enzyme that is located on the host cell surface. To gain entry into a target cell, the SARS-CoV S protein binds to the ACE2 receptor.…”
Section: Key Nonstructural Proteinsmentioning
confidence: 99%
“…As per the viral cycle, upon entry into the host cell, the incoming viral genome is initially translated to produce two large precursor polyproteins 1a (pp1a) and 1ab (pp1ab), that are processed by ORF 1a-encoded viral proteinases, papain-like protease (PLpro), and the 3-chymotrypsin-like cysteine protease (Mpro or 3CLpro) into 16 mature non-structural proteins (NSP1-NSP16) 22 . Many of the NSPs perform essential functions in viral RNA replication and translation 22 , 23 , 24 . The 3CLpro enzyme, a.k.a.…”
Section: Introductionmentioning
confidence: 99%